Real-time DDoS detection in software-defined networks using machine learning - Hasan, Kadir; Hossain, Kaji Sajjad; Apurbo, GM Mohaiminuzzaman; Islam, MD Zubairul; Alam, Md Shakibul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.